2011
DOI: 10.1007/s00595-010-4553-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing intraoperative blood flow in cardiovascular surgery

Abstract: Off-pump coronary arterial bypass grafting and new surgical apparatus and techniques have decreased the mortality rate associated with this procedure to approximately 1.5%. If we could detect problems in the constructed coronary anastomoses by an alternative imaging system to coronary angiography during surgery, decisions to revise the surgical procedure could be made without hesitation. Meanwhile, the intraoperative direct evaluation of intestinal blood flow during abdominal aortic aneurysmal surgery is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…During this time ICG binds to plasma proteins, and the pericardial coronary arteries brightly fluoresce. An occlusion in the coronary circulation is seen as a perfusion defect with no fluorescence in the vessel [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…During this time ICG binds to plasma proteins, and the pericardial coronary arteries brightly fluoresce. An occlusion in the coronary circulation is seen as a perfusion defect with no fluorescence in the vessel [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…Use of ICG angiographic imaging has been previously examined for monitoring vascular perfusion in animals and humans, thus forming the foundation of the SPY Imager device that is primarily used to monitor vascular reanastamoses during different surgical procedures (13,16,20,24,29). However, in this study we found that the SPY Imager was very capable and useful for performing serial measurements of vascular perfusion of ICG that allowed for enhanced imaging of vascular remodeling responses in situ over time.…”
Section: Discussionmentioning
confidence: 85%
“…The camera was placed 30-50 cm above the surgical field and ICG 0.05 mg/kg was injected via a central venous catheter followed by 10 mL saline for flushing [7,8]. We performed conventional qualitative HEMS assessment intraoperatively in all patients and the opacification was categorized as excellent or abnormal, qualitatively [7,8].…”
Section: Surgical Strategy and Intraoperative Assessmentmentioning
confidence: 99%
“…To check the quality of anastomosis intraoperatively, we use indocyanine green (ICG) angiography, which is a contrast study for visualizing the blood flow through a near-infrared camera, with an intravenous injection of ICG contrast agent, in addition to the commonly used transit time flowmeter (TTF) [2][3][4][5]. Since 2008, we have been using the angiography equipment HyperEye Medical System (HEMS; MNIRC-1000; Mizuho Ikakogyo, Co., Ltd, Tokyo, Japan) as an ICG angiographic device in cardiovascular surgery, including CABG [6,7].…”
Section: Introductionmentioning
confidence: 99%